1991
DOI: 10.1152/ajpendo.1991.261.6.e809
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in skeletal muscle and whole body in response to euglycemic hyperinsulinemia in normal adults

Abstract: To simultaneously assess the relative antiproteolytic effect of insulin on both skeletal muscle and in the whole body, phenylalanine rates of appearance (Ra; reflecting proteolysis) were measured across the leg (reflecting skeletal muscle) and in the whole body, utilizing a constant tracer infusion of [2H5]phenylalanine in the basal state and during euglycemic hyperinsulinemia (2,600 microU/ml) in seven normal adults. Phenylalanine Ra in the leg was significantly decreased during hyperinsulinemia (6.11 +/- 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
3
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 11 publications
5
62
3
1
Order By: Relevance
“…These results are also supported by other studies [17, 20, Louard et al(a) 1992 [19] Fryburg et al 1995 [26] Timmerman et al (1b) 28-31, 34, 44]. In all healthy human studies where AA availability has been reduced, MPS has been reduced or remained unchanged [18,19,37,45,46], even in the presence of supraphysiological concentrations of insulin [18]. The meta-analysis of the 25 studies showed that insulin exerts its regulation of lean muscle mass principally via an anticatabolic effect in reducing MPB.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are also supported by other studies [17, 20, Louard et al(a) 1992 [19] Fryburg et al 1995 [26] Timmerman et al (1b) 28-31, 34, 44]. In all healthy human studies where AA availability has been reduced, MPS has been reduced or remained unchanged [18,19,37,45,46], even in the presence of supraphysiological concentrations of insulin [18]. The meta-analysis of the 25 studies showed that insulin exerts its regulation of lean muscle mass principally via an anticatabolic effect in reducing MPB.…”
Section: Discussionsupporting
confidence: 82%
“…The role of insulin in adult human skeletal muscle is more complex and subject to interplay between other factors such as AA availability, muscle blood flow and microvascular recruitment [16,17]. This has led to various studies reporting opposing conclusions when it comes to the relationship between insulin and human skeletal muscle protein turnover [16][17][18][19][20][21][22]. We therefore undertook a systematic review and meta-analysis in an attempt to clarify the role of insulin in regulating muscle metabolism in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported an increase in human muscle protein synthesis in response to insulin (1,2,17,25,27,42). However, others have reported an inhibition of muscle proteolysis with no significant changes in muscle protein synthesis (11,14,16,23,24). We (44) have previously hypothesized that these different results might be explained by differences in amino acid availability.…”
mentioning
confidence: 86%
“…Therefore, the studies that report an increase in muscle protein synthesis by insulin infusion also show an increased amino acid delivery to the muscle (1,2,15,17,25,27,42). Interestingly, most studies reporting no change in amino acid delivery and/or a reduction in blood amino acid concentrations with systemic insulin infusion also report that muscle proteolysis is inhibited (11,16,23,24).We hypothesized that insulin and nutritional energy stimulate skeletal muscle protein synthesis provided that blood amino acid availability is not reduced. To test our hypothesis, we examined the differential effects of an amino acid-lowering systemic insulin infusion with a high-energy clamp (hyperglycemic hyperlipidemic) vs. a local insulin infusion in the femoral artery with a low-energy euglycemic clamp that did not induce major decreases in blood amino acid concentrations.…”
mentioning
confidence: 96%
“…[8][9][10]20,21 In the pediatric population, one previous study measured the effects of insulin on protein metabolism in a cohort of 4 extremely low-birth-weight neonates. 22 The investigators showed a 20% reduction in protein breakdown, although this was associated with a corresponding decrease in protein synthetic rate.…”
Section: Discussionmentioning
confidence: 99%